Upaya Pelestarian dan Pengembangan Wisata Edukasi Jabu Sihol Pematang Siantar - Elsa Dameria Naibaho; Fahri Irfarizki Siregar; Fidia Chairany Sitorus; Julwandi Simarmata; Maya Anggreani Viollita Purba; Randa Wijaya; Valentino Girsang; Dian G Purba Tambak (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
Indonesia has many forms of society that differ from one another. And on the island of Sumatra, especially North Sumatra, there are several forms of society that still adhere to customs and culture very well in this era of globalization and modernity. One of them is the Education Village in North Sumatra Province, precisely in Pematang Siantar, namely, Jabu Sihol. Jabu Sihol Educational Village, apart from being a cultural village that still has cultural heritage, is also a tourist village that tourists can visit. Jabu Sihol is a project located in Pematangsiantar, in northern Sumatra, Indonesia. Jabu Sihol tourist village has interesting education for tourists, namely cultural education and cultivation education. This research aims to determine tourism education in the Jabu Sihol tourist village and to determine the development of education. The research method used was field research, observation and interviews with management. The results obtained from this research are that the Jabu Sihol tourist village has cultural tourism education in the form of Ulos weaving, learning Batak script, Batak dance, typical Tapanuli cuisine and cultivation education in the form of farming, fish cultivation and ABF maggots. The educational development carried out is the development of cultural education and cultivation education.